Long-term outcome of free fibula osteocutaneous flap and massive allograft in the reconstruction of long bone defect. Issue 12 (December 2015) - Halim, Ahmad Sukari; Chai, Siew Cheng; Wan Ismail, Wan Faisham; Wan Azman, Wan Sulaiman; Mat Saad, Arman Zaharil; Wan, Zulmi
Summary: Reconstruction of massive bone defects in bone tumors with allografts has been shown to have significant complications including infection, delayed or nonunion of allograft, and allograft fracture. Resection compounded with soft tissue defects requires skin coverage. A composite osteocutaneous free fibula offers an optimal solution where the allografts can be augmented mechanically and achieve biological incorporation. Following resection, the cutaneous component of the free osteocutaneous fibula flaps covers the massive soft tissue defect. In this retrospective study, the long-term outcome of 12 patients, who underwent single-stage limb reconstruction with massive allograft and free fibula osteocutaneous flaps instead of free fibula osteal flaps only, was evaluated. This study included 12 consecutive patients who had primary bone tumors and had follow-up for a minimum of 24 months. The mean age at the time of surgery was 19.8 years. A total of eight patients had primary malignant bone tumors (five osteosarcomas, two chondrosarcomas and one synovial sarcoma), and four patients had benign bone tumors (two giant-cell tumors, one aneurysmal bone cyst, and one neurofibromatosis). The mean follow-up for the 12 patients was 63 months (range 24–124 months). Out of the 10 patients, nine underwent lower-limb reconstruction and ambulated with partial weight bearing and full weight bearing at an average of 4.2 months and 8.2 months, respectively. In conclusion, augmentation of a massive allograft with free fibula osteocutaneous flap is an excellent alternative for reducing the long-term complication of massive allograft and concurrently addresses the soft tissue coverage.